2021
DOI: 10.1093/nutrit/nuaa125
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional associations between sleep quality or quantity, and dietary intakes or eating behaviors in children 6–12 years old: a systematic review with evidence mapping

Abstract: Context Although dietary advice has long been a cornerstone of a healthy lifestyle, how sleep quality and quantity may interact with dietary intake or eating behaviors remains unclear. Objective To consider a bidirectional relationship between sleep and diet in children aged 6–12 years via a systematic review following PRISMA guidelines. Data Sources Relevant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Sleep debt studies have also shown an increase in food craving, suggesting that EB changes can occur by eating behaviorrelated aspects (121,122). These findings were confirmed in epidemiological studies (123,124) and recent systematic reviews, which have shown that sleep debt promotes worse food choices (i.e., snacks, sugar, fat) (125,126). Moreover, indirect pathways mediated by sleep debt can also affect food intake.…”
Section: Short Sleep Durationmentioning
confidence: 73%
“…Sleep debt studies have also shown an increase in food craving, suggesting that EB changes can occur by eating behaviorrelated aspects (121,122). These findings were confirmed in epidemiological studies (123,124) and recent systematic reviews, which have shown that sleep debt promotes worse food choices (i.e., snacks, sugar, fat) (125,126). Moreover, indirect pathways mediated by sleep debt can also affect food intake.…”
Section: Short Sleep Durationmentioning
confidence: 73%
“…In the current study, we observed differences in macronutrient composition, which supports the findings of some [ 32 , 34 ], but not all [ 33 , 35 , 38 ] previous studies, although it could be argued that macronutrient differences are unlikely unless energy intake has also changed significantly. Although a reasonable body of observational literature indicates that short sleep is associated with lower dietary quality [ 39 , 40 ], the bulk of this research is cross-sectional in nature and thus unable to determine causality. Our finding that the increased caloric intake was mostly due to increases in non-core or ultraprocessed foods rather than core foods, as well as sweetened beverages [ 16 ] supports existing experimental research in adolescents [ 34 , 38 ] and adds support to these observational findings [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings indicate that for some children with early night time sleep timing there is an elevated risk for adiposity. It is possible that either the sleep timing among these children is suboptimal in relation to their sleep need or the combination of timing and quality of food in relation to their sleep timing might increase the risk for adiposity among these children (Ward et al, 2021). Further studies on the interplay between preschool children's nutrition and sleep on health is required.…”
Section: Discussionmentioning
confidence: 99%